INCIDENCE AND FACTORS ASSOCIATED WITH BLOOD TRANSFUSION IN A SAMPLE OF SOUTH AFRICAN PATIENTS UNDERGOING PRIMARY HIP ARTHROPLASTY: A RETROSPECTIVE DATABASE STUDY. - Essa, Safwana; Ramburuth, Marsha; Moodley, Yoshan (Student's Journal of Health Research Africa, 2023)
Background: Despite improvements in arthroplasty and blood conservation practices, surgical blood loss remains a challenge. The blood products used to address perioperative bleeding are scarce and should be effectively managed. Our study objectives were to 1) establish the cumulative incidence of peri-operative transfusion in a sample of South African primary hip arthroplasty patients and 2) identify factors associated with transfusions. Methods: This study was a sub-analysis of an existing database of 174 adult primary hip arthroplasty patients who underwent surgery at Inkosi Albert Luthuli Central Hospital between 01 January 2015 and 30 June 2016. A retrospective chart review process was used to collect the data analyzed using descriptive statistical methods, Mann-Whitney testing, and Chi-squared testing. The study outcome was perioperative blood transfusion, defined as receipt of at least 1 unit of packed red cells anytime between the surgical incision and discharge from the hospital. Results: The incidence of perioperative blood transfusion was 13.8% (95%CI: 9.0-19.8%). The median number of blood units received was 2.0 (Range: 1.0-4.0) units. The proportion of patients who received blood transfusions was higher in those who had longer surgery (41.7% vs. 14.7 % p=0.002) or received postoperative thromboprophylaxis (91.7% vs. 68% p=0.017). Conclusion: The incidence of perioperative blood transfusion observed in our study of patients undergoing primary hip arthroplasty was within range of that reported in international studies. Longer surgery and postoperative thromboprophylaxis are potentially important predictors of perioperative transfusion following hip arthroplasty in our setting. We recommend further research to confirm our findings.